Impact of soil texture and water availability on the hydraulic control of plant and grape-berry development - Tramontini, Sara; van Leeuwen, Cornelis; Domec, Jean-Christophe; Destrac-Irvine, Agnès; Basteau, Cyril; Vitali, Marco; Mosbach-Schulz, Olaf; Lovisolo, Claudio (Plant and soil, 2013)
Aims All components of the soil-plant-atmosphere (s-p-a) continuum are known to control berry quality in grapevine (Vitis vinifera L.) via ecophysiological interactions between water uptake by roots and water loss by leaves. The scope of the present work was to explore how the main hydraulic components of grapevine influence fruit quality through changes in liquid- and gas-phase hydraulic conductance. Methods To reach our objectives, determinations of shoot growth, berry size and sugar content, leaf gas exchange, predawn leaf water potential (as a proxy of soil water potential), midday stem water potential and leaf water potential were performed in conjunction with anatomical measurements of shoot xylem. All measurements were conducted in two different cultivars (Cabernet franc and Merlot) and on three different soil types (clayey, gravelly, and sandy). Results Shoot xylem morphometric characteristics and whole-plant hydraulic conductance were influenced by cultivar and soil type. Differences in leaf gas exchange parameters and water potentials were determined by soil type significantly more than by cultivar. Between the two extremes (gravelly soil imposing drought conditions and sandy soil with easily accessible water) the clayey soil expressed an intermediate plant water consumption and highest sugar accumulation in berry. Conclusions Hydraulic and non hydraulic limitations to vine/berry interactions supported the conclusion that water availability in the soil overrides differences due to cultivar in determining the productive potential of the vineyard. Non hydraulic stomatal control was expected to be an important component on plants grown on the clayey soil, which experienced a moderate water stress. Possible links between hydraulic traits and berry development and quality are discussed.